2013
DOI: 10.1177/0734904113514810
|View full text |Cite
|
Sign up to set email alerts
|

Flammability limits of biogenic volatile organic compounds emitted by fire-heated vegetation (Rosmarinus officinalis) and their potential link with accelerating forest fires in canyons: A Froude-scaling approach

Abstract: The accelerating forest fire phenomenon for two real accidents is studied. This phenomenon is investigated using the thermochemical hypothesis, based on the ignition of a biogenic volatile organic compounds cloud accumulated in canyons. By heating a Rosmarinus officinalis plant in a specific hermetic enclosure, a mixture of 14 biogenic volatile organic compounds is identified and their mass fractions determined as temperature functions. The theoretical flammability limits of those components are calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The bench-scale flammability experiments offer a limited insight on wildfire behaviour (Fernandes & Cruz 2012). Nevertheless, some modelling approaches based on Froudescaling (Chetehouna et al 2014) suggested that the results of flammability experiments and the implication of BVOCs could be potentially applied in field conditions. In this sense, physics-based models of flammability have the potential to deal with a continuous range of fuel properties and should allow to better understand the impact of fuel dynamics on wildfire spread (Fares et al 2017).…”
Section: Relationship Between Flammability Terpenoids and Fmcmentioning
confidence: 99%
See 1 more Smart Citation
“…The bench-scale flammability experiments offer a limited insight on wildfire behaviour (Fernandes & Cruz 2012). Nevertheless, some modelling approaches based on Froudescaling (Chetehouna et al 2014) suggested that the results of flammability experiments and the implication of BVOCs could be potentially applied in field conditions. In this sense, physics-based models of flammability have the potential to deal with a continuous range of fuel properties and should allow to better understand the impact of fuel dynamics on wildfire spread (Fares et al 2017).…”
Section: Relationship Between Flammability Terpenoids and Fmcmentioning
confidence: 99%
“…Contrastingly, more complex physical models like FIRETEC (Linn et al 2002) take into account gaseous-by products of forest fires, but no study has been carried out to assess the influence of terpenoids in fire behaviour using these multiphase models. More recently, the influence of terpenoids in accelerating forest fires has been evidenced at laboratory scale (Chetehouna et al 2009) and modelled at larger scales (Chetehouna et al 2014). Viegas & Simeoni (2010) also hypothesize gas accumulation due to the production of volatile organic compounds as one of the possible causes of eruptive fires.…”
Section: Introductionmentioning
confidence: 99%
“…Monoterpene LFLs are located around 0.7 %vol (Barboni, 2006;Chetehouna et al, 2014; Catoire & Naudet, 2005) (7.10 -3 ݉ ை ଷ /݉ ௧௧ ଷ ). Therefore, a factor of 3.10 4 is needed to obtain a flammable atmosphere during spring in Valencia (Spain).…”
Section: Extrapolation To Real Casementioning
confidence: 99%
“…In presence of a fire, the natural emission of volatile organic compounds (VOC) by the vegetation increases due to thermal stress (e.g. Chetehouna et al 2014). Then, the turbulent exchange mechanism between the forest area and the free atmosphere is likely to release highly concentrated gas pockets above the forest where they may find favourable conditions for their ignition.…”
Section: Introductionmentioning
confidence: 99%